Problem Based-Learning To Improve Mathematical Abilities In The Context Of Forming The Critical Thinking Character Of Elementary School Students - Najoan, R A O (Universitas Negeri Manado, 2019)
Problem-based learning math is forming children critical thinking in solving problems. Therefore, it can make children whose character so as to answer the question of educational quality improvement is expected in particular on education in elementary schools. The purpose of this research is to develop a problem-based learning math in elementary school. This study uses classroom action research approach. The results obtained in this study showed an increase in math skills of elementary school studentsÂ Keywords: mathematical ability; students; Problem-Based Learning.